Answer:
x ’= 1,735 m, measured from the far left
Explanation:
For the system to be in equilibrium, the law of rotational equilibrium must be fulfilled.
Let's fix a reference system located at the point of rotation and that the anticlockwise rotations have been positive
They tell us that we have a mass (m1) on the left side and another mass (M2) on the right side,
the mass that is at the left end x = 1.2 m measured from the pivot point, the mass of the right side is at a distance x and the weight of the body that is located at the geometric center of the bar
x_{cm} = 1.2 -1
x_ {cm} = 0.2 m
Σ τ = 0
w₁ 1.2 + mg 0.2 - W₂ x = 0
x =
x = ![\frac{m_1 \ 1.2 \ + m \ 0.2 }{M_2}](https://tex.z-dn.net/?f=%5Cfrac%7Bm_1%20%5C%201.2%20%5C%20%2B%20m%20%5C%200.2%20%7D%7BM_2%7D)
let's calculate
x =
2.9 1.2 + 4 0.2 / 8
x = 0.535 m
measured from the pivot point
measured from the far left is
x’= 1,2 + x
x'= 1.2 + 0.535
x ’= 1,735 m
<span>Suppose that an electric charge is produced on one part of a body. If the charge spreads through the entire body, the body is most likely made of metal. </span>
Answer:
length of the ladder is 13.47 feet
base of wall to latter distance 6.10 feet
angle between ladder and the wall is 26.95°
Explanation:
given data
height h = 12 feet
angle 63°
to find out
length of the ladder ( L) and length of wall to ladder ( A) and angle between ladder and the wall
solution
we consider here angle between base of wall and floor is right angle
we apply here trigonometry rule that is
sin63 = h/L
put here value
L = 12 / sin63
L = 13.47
so length of the ladder is 13.47 feet
and
we can say
tan 63 = h / A
put here value
A = 12 / tan63
A = 6.10
so base of wall to latter distance 6.10 feet
and
we say here
tanθ = 6.10 / 12
θ = 26.95°
so angle between ladder and the wall is 26.95°
Answer:
a) 1.3 rad/s
b) 0.722 s
Explanation:
Given
Initial velocity, ω = 0 rad/s
Angular acceleration of the wheel, α = 1.8 rad/s²
using equations of angular motion, we have
θ2 - θ1 = ω(0)[t2 - t1] + 1/2α(t2 - t1)²
where
θ2 - θ1 = 53.2 rad
t2 - t1 = 7s
substituting these in the equation, we have
θ2 - θ1 = ω(0)[t2 - t1] + 1/2α(t2 - t1)²
53.2 =ω(0) * 7 + 1/2 * 1.8 * 7²
53.2 = 7.ω(0) + 1/2 * 1.8 * 49
53.2 = 7.ω(0) + 44.1
7.ω(0) = 53.2 - 44.1
ω(0) = 9.1 / 7
ω(0) = 1.3 rad/s
Using another of the equations of angular motion, we have
ω(0) = ω(i) + α*t1
1.3 = 0 + 1.8 * t1
1.3 = 1.8 * t1
t1 = 1.3/1.8
t1 = 0.722 s
The answer is c you got to look for answers that make sense